Are both individual-level and county-level social capital associated with individual health? A serial cross-sectional analysis in China, 2010–2015 - Yang Han (BMJ Open)
Objectives We aimed to examine the associations of both individual-level and county-level social capital with individual health in China during a period of rapid economic growth.Design and setting A serial cross-sectional study in China.Participants and methods The participants were 42 829 Chinese adults (aged ≥18 years) from the 2010, 2012, 2013 and 2015 Chinese General Social Survey. The outcomes were self-rated physical and mental health in all time points. We assessed social capital by the individual-level and county-level indicators, including frequency of socialising, civic participation and trust. We conducted multilevel binary logistic regression models to examine the associations of individual-level and county-level social capital with self-rated physical and mental health.Results At the individual level, high frequency of socialising (2010—OR: 1.49, 95% CI: 1.33 to 1.66; 2012—OR: 1.39, 95% CI: 1.26 to 1.54; 2013—OR: 1.28, 95% CI: 1.15 to 1.42; 2015—OR: 1.36, 95% CI: 1.23 to 1.50) and high trust (2010—OR: 1.34, 95% CI: 1.22 to 1.47; 2012—OR: 1.30, 95% CI: 1.18 to 1.42; 2013—OR: 1.21, 95% CI: 1.10 to 1.33; 2015—OR: 1.41, 95% CI: 1.28 to 1.55) was significantly associated with good physical health in all years. At the individual level, high frequency of socialising (2010—OR: 1.27, 95% CI: 1.14 to 1.42; 2012—OR: 1.21, 95% CI: 1.09 to 1.34; 2013—OR: 1.30, 95% CI: 1.17 to 1.45; 2015—OR: 1.35, 95% CI: 1.22 to 1.50) and high trust (2010—OR: 1.47, 95% CI: 1.34 to 1.61; 2012—OR: 1.42, 95% CI: 1.30 to 1.56; 2013—OR: 1.36, 95% CI: 1.24 to 1.49; 2015—OR: 1.43, 95% CI: 1.30 to 1.57) was also significantly associated with good mental health in all years. No evidence showed that the associations of individual-level frequency of socialising and trust with physical and mental health changed over time. There were no consistent associations of individual-level civic participation or any county-level social capital indicators with physical or mental health.Conclusion The positive associations of individual-level social capital in terms of socialising and trust with physical and mental health were robust during a period of rapid economic growth. Improving individual-level socialising and trust for health promotion could be a long-term strategy even within a rapidly developing society.